Corrosion Study of Steels In Liquid Lead-Bismuth Cooled Nuclear Reactors by Computer Simulation using Moldy Code - Alan Maulana; Zaki Su'ud; Hermawan K. Dipojono; Khairurrijal Khairurrijal (Institut Teknologi Bandung, 2007)
The corrosion of steel in liquid lead-bismuth has been studied by computer simulation using MOLDY code. The diffusion processes among atoms are assumed to be the key issues to understand the corrosion mechanism microscopically. In order to simulate these diffusion processes, the inter-atomic potential between Fe-Fe, Pb-Pb, Bi-Bi, Cr-Cr and Ni-Ni are assumed to obey the Lennard-Jones potential. The Lennard-Jones potential parameters of above pairs of atom have been derived by fitting the data available in the literature with the Lennard-Jones equation. The initial positions of the system are taken from the crystal structures data including the cell parameters. The simulation cell was a box with the volume 60x30x30 Å3 that were filled by 2864 atoms. Nickel and chromium atoms were substituted into Fe crystal with the percentage 10% and 16 % respectively to construct the systems of SS-316 which contacted by 50%Pb-50%Bi. The molecular dynamic simulations have been carried out for surface interaction between steel crystal with liquid lead-bismuth for several temperatures. After done the above simulation, the simulation is then tried by using 45%Pb-55%Bi (Pb-Bi Eutectic). The results of molecular dynamic simulations for several temperatures and the effect of variation of Pb and Bi above will be presented in this paper.